The Role of Adat Justice and Its Adat Institutons in Preventing Transnational Crimes in Aceh Province, Indonesia - Sri Walny Rahayu (Kanun Jurnal Ilmu Hukum, 2017)
More than one decade after Law Number 11/2006 on the Government of Aceh entered into force, the adaptive ability of adat justice and acehnese adat institutions survived because of their strong legal basis in indonesian laws and regulations. On the other hand, the implementation of the Asean Economy Community (AEC) since December 31, 2015, imposes threats like the emergence of various forms of transnational crime that crosses national boundaries, committed by perpetrators from two or more countries with modern modus operandi. The enactment of the  AEC in Aceh poses a challenge to exploit the opportunities adat justice and adat institute to anticipate such crimes. Based on data from the Asean Plan of Action to Combat Transnational Crime (ASEAN-PACTC), There are eight (8) types of transnational organized crime, illicit drug trafficking, human trafficking, sea piracy, arms smuggling, money laundering, terrorism, international economic crime and cyber crime. This paper describes the adaptive ability of adat justice, and acehnese adat institute and intervention model of adat justice in aceh, the era of AEC in facing transnational crime. The power of adat justice and acehnese adat institutions should be expanded facing - the challenges - of transnational crime as a result of the implementation of the AEC in Indonesia Peradilan Adat dan Lembaga Adat dalam Pencegahan Kejahatan Transnasional di Provinsi Aceh, Indonesia Lebih dari satu dekade setelah berlakunya Undang-Undang No. 11 Tahun 2006 tentang Pemerintahan Aceh, kemampuan adaptif peradilan adat dan lembaga adat Aceh terus bertahan karena memiliki dasar legalitas penormaan yang kuat diatur dalam undang-undang dan peraturan di Indonesia. Di sisi lain jika dikaji, konsekuensi pelaksanaan Masyarakat Ekonomi Asean (MEA) efektif berlaku 31 Desember 2015 di Indonesia berpotensi menimbulkan ancaman seperti munculnya berbagai bentuk kejahatan transnasional yang melintasi perbatasan suatu negara, dilakukan oleh pelaku dari dua atau lebih negara dengan modus operandi modern. Berlakunya MEA bagi Aceh merupakan tantangan memanfaatkan peluang peradilan adat dan lembaga adat mengantisipasi kejahatan tersebut. Berdasarkan data dari ASEAN Rencana Aksi untuk memerangi kejahatan transnasional terdapat delapan bentuk kejahatan yaitu, perdagangan gelap narkoba, perdagangan manusia, laut-pembajakan, penyelundupan senjata, pencucian uang, terorisme, kejahatan ekonomi internasional dan cyber crimes. Tulisan ini bertujuan menjelaskan kemampuan adaptif peradilan adat, lembaga adat Aceh, dan model intervensi peradilan adat di Aceh menghadapi kejahatan transnasional era MEA.